Late failure of cerebral autoregulation in hypoxic-ischemic encephalopathy is associated with brain injury: a pilot study. (7th December 2018) - Vesoulis, Zachary A; Liao, Steve M; Mathur, Amit M
Abstract: Background : Post-resuscitation reperfusion following hypoxic-ischemia (HIE) is associated with secondary brain injury in neonates. Objective : To quantify the association between perfusion exceeding autoregulatory limits and brain injury. Approach : Continuous mean arterial blood pressure (MABP) and cerebral near-infrared spectroscopy (NIRS) data were prospectively collected from infants with HIE. Cerebral oximetry index (COx) was calculated as a moving correlation coefficient between MABP and NIRS. Upper and lower limits of autoregulation were identified by transition from negative to positive correlation. The proportion of time MABP above (hyperperfusion) and below (hypoperfusion) autoregulatory limits was calculated during therapeutic hypothermia (days 1–3). Main results : Sixteen infants were included; injury was noted in 7/16. There was no significance in hyperperfusion burden between injured and uninjured infants during day one (7% versus 10%, p   =  0.88) or two (4% versus 2%, p   =  0.88), but there was a marked increase for injured infants on day three (54% versus 14%, p   =  0.02). There was a corollary decrease in hypoperfusion for injured versus uninjured infants on day 3 (6% versus 24%, p   =  0.05). Significance : HIE infants with brain injury have a late failure of cerebral autoregulation, manifested as a hyperperfusion burden, suggesting pathologic events are active on day 3 of hypothermia. This finding may help to identify infants which might need additional neuroprotection.